Absence of postmating barriers between a selfing vs. outcrossing Chilean Mimulus species pair. Issue 6 (24th May 2016) - Stanton, Kimmy; Valentin, Celine M.; Wijnen, Marijke E.; Stutstman, Sage; Palacios, Jessica J.; Cooley, Arielle M.
Abstract : PREMISE OF THE STUDY: Reproductive isolation between sympatric species pairs may be maintained by both pre‐ and postmating barriers. Here we evaluate potential barriers to mating between the outcrossing Mimulus luteus and its more highly selfing sympatric congener, M. cupreus, two members of the South American luteus complex of Mimulus . METHODS: Seed set was compared following autonomous self‐pollination, manual pollination, conspecific outcrossing, and sympatric and allopatric hybridization, for laboratory‐maintained inbred lines and wild‐collected accessions. Survival and reproductive fitness of hybrids relative to parental species were examined across environments that differed with respect to temperature and soil nutrients, two factors that vary across the ranges of M. luteus and M. cupreus . KEY RESULTS: Mimulus luteus was minimally capable of autonomous self‐fertilization, consistent with reliance on an animal pollinator, whereas M. cupreus was a successful selfer across all tested accessions. Postmating barriers to hybridization are negligible, in both low‐ and high‐stress environments, across multiple sympatric and allopatric populations. CONCLUSION: As in the North American M. guttatus – M. nasutus species pair, postmating barriers contribute little to isolation between M. luteus and M. cupreus . This result reinforces the importance of premating barriers, specifically species differences in reliance on, and accessibility to, animal pollinators. A unique aspect of the M. luteus – M. cupreus pair is the recent gain of red floral anthocyanin pigmentation in M. cupreus . On the basis of species differences in vegetative anthocyanin production, a facultative stress‐protective response, we propose a potential stress‐protective role for the constitutive floral anthocyanins of M. cupreus .